SCREENING OF HERBICIDES FOR WEED MANAGEMENT IN TRANSPLANTED RICE - M. M. Ashraf; T. H. Awan; Z. Manzoor; M. Ahmad; M. E. Safdar (Journal of Animal and Plant Sciences, 2006)
Studies for weed management in transplanted rice were carried out at the experimental farm of Rice Research Institute, Kala Shah Kaku, Lahore during the Kharif seasons of 2004 and 2005 to find out the best strategy for weed control in transplanted rice (Oryza sativa L.). The experiment was laid out in randomized complete block design and replicated thrice with a net plot size of 10X5 m2. During both the years newly released rice variety Basmati-2000 was used as an experimental material. The nursery was transplanted during second week of July. Six herbicides applied at 4th day of transplanting were compared with weedy check in which no weeds were eradicated as well as with manual hand weeding at 22 DAT. Highest weed control ( (93.03%) was recorded in case of sunstar during first year, while during the second year the maximum control of weeds was 94.67 % in case of hand weeding. Regarding number of tillers/plant, hand weeding resulted into 21.4 and 20.8 for the year 2004 and 2005 in comparison to 15.3 and 16.6 for control (weedy check) for first and second year of the experiment, respectively. Where as the highest number of grains / panicle was recorded 132.56 during first year (2004) and 135.50 during the second year (2005). All of the herbicidal treatments did not differ significantly from hand weeding during both the years for this character. In terms of paddy yield, hand weeding gave the highest grain yield but remained statistically at par with certain herbicides. Welchlore and declore gave lower yield for the year 2004 and 2005, respectively. Control (weedy check) produced the lowest yield during both the years.
Keywords: Herbicides; Oryza sativa L. Weeds.